Analysis of bank “X” business plan: Assessment of process appropriateness and evaluation of manager motivation - Elizabeth Tri Utami Kurniawati; Dwi Hartanti (The Indonesian Accounting Review, 2024)
The bank business plan is a short and medium term bank strategic planning tool that must be prepared by the bank annually. The bank business plan functions not only as a company strategic planning tool for internal purposes, but also as a compliance report to relevant government agencies. With these two different functions, managers have the task of ensuring that the information in the bank business plan meets government compliance and does not reduce the company’s superiority in the banking industry. Therefore, this research aims to evaluate the accuracy and suitability of the process in preparing the bank business plan and analyze the motivation for disclosing information in the bank business plan. This research is a pioneering study that evaluates the process of preparing a bank business plan from the perspective of the bank business plan as a strategic planning tool and relates it with an analysis of motivation to disclose information using the perspective of the bank business plan as a regulatory compliance tool. This research uses a case study method with Bank “X” as the unit of analysis. The results of this research indicate that the business plan preparation process at Bank “X” has met 80% of the appropriateness criteria for the strategic plan process. Meanwhile, the motivation to disclose information in Bank “X”’s business plan tends to indicate a signal of intent. This research also reveals several things that can improve the process of preparing a bank business plan and its benefits for Bank “X”.